2008
DOI: 10.1007/s00497-008-0088-6
|View full text |Cite
|
Sign up to set email alerts
|

Diploid endosperm formation in Tulipa spp. and identification of a 1:1 maternal-to-paternal genome ratio in endosperms of T. gesneriana L.

Abstract: Most Liliaceae plants have the tetrasporic Fritillaria-type embryo sac and normally form diploid embryos and pentaploid endosperms derived from a 4:1 maternal-to-paternal genome ratio (4m:1p) after double fertilization. Here we characterize embryo sac and endosperm formation in Tulipa spp. of Liliaceae. Chromosome analysis using seeds derived from 2x x 2x crosses of Tulipa gesneriana (2n = 2x = 24) identified diploid chromosome number in the endosperm. Similarly, flow cytometric analysis confirmed diploid endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…While tulip may be an appropriate Fritillaria-type for comparison, only few works on tulip hybridization have been reported (Van Eijk et al 1991;Van Creij et al 1997, and even fewer on tulip 3x 9 2x/ 4x crosses (Mizuochi et al 2009). Mizuochi et al did observe, however, that the ratio of embryo and endosperm ploidy level of 2x 9 2x or 3x 9 2x in tulip is invariably 1:1.…”
Section: Discussionmentioning
confidence: 97%
“…While tulip may be an appropriate Fritillaria-type for comparison, only few works on tulip hybridization have been reported (Van Eijk et al 1991;Van Creij et al 1997, and even fewer on tulip 3x 9 2x/ 4x crosses (Mizuochi et al 2009). Mizuochi et al did observe, however, that the ratio of embryo and endosperm ploidy level of 2x 9 2x or 3x 9 2x in tulip is invariably 1:1.…”
Section: Discussionmentioning
confidence: 97%
“…Because the central cell of most flowering plant species is homodiploid (2 x ) and fertilized by a haploid male gamete ( x ), the resulting endosperm is triploid (2 + 1) and, therefore, genetically distinct from the diploid embryo (1 + 1). The endosperm of most angiosperms is triploid, with a 2:1 ratio of the maternal to the paternal genome, although exceptions have been found in some species (Williams and Friedman, 2002; Mizuochi et al , 2009). Endosperm is particularly sensitive to ploidy unbalance (Köhler et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In lilies, these crosses resulted in all triploid or near-triploid seedlings derived from viable 2n gametes from triploid male parents (Marasek-Ciolakowska et al, 2014). In Tulipa, 2x • 3x crosses yielded a majority of diploid and near-diploid progeny with a small percent of neartriploids (Mizuochi et al, 2009). This same study found that the reciprocal cross in Tulipa yielded a binomial distribution of aneuploids, with the female triploid parent producing a wide range of fertile aneuploids (Mizuochi et al, 2009).…”
Section: Series Zmentioning
confidence: 77%
“…In Tulipa, 2x • 3x crosses yielded a majority of diploid and near-diploid progeny with a small percent of neartriploids (Mizuochi et al, 2009). This same study found that the reciprocal cross in Tulipa yielded a binomial distribution of aneuploids, with the female triploid parent producing a wide range of fertile aneuploids (Mizuochi et al, 2009). Similar to lilies, 2x • 3x crosses in Allium schoenoprasum (Levan, 1936) and C. sativus (Diao et al, 2009) resulted in diploids or neardiploids with a small percent of near-triploids; the reciprocal crosses yielded a wider range of aneuploids.…”
Section: Series Zmentioning
confidence: 99%